Doing Internet Research: Critical Issues and Methods for Examining the Net - Jones, Steven (SAGE Publications, Incorporated, 1998)
The Internet is a medium with great consequences for social and economic life. This book is written to help people discern in what ways it has commanded the public imagination, and the methodological issues that arise when one tries to study and understand the social processes occurring within it.
https://katalog.adlr.link/Record/76-EBC996902